The Legal Review on the Sale of Land Auction Results When A Breach Happened - Rahmalia, Riza Septi (Jurnal Konstatering, 2022)
Any collateralized credit in the form of land rights must be collateralized by a mortgage right as outlined in the Mortgage Granting Deed (APHT), for granting a certain amount of credit. APHT is made, then the promise will legally bind both parties so that they can anticipate in the event of a default. Normative juridical approach method. Specifications are analytical descriptive. The type of data is secondary data, divided into legal material originating from law and legal knowledge. The method of collecting data through literature studies and interviews with data analysis methods is qualitative analysis. The legal review of the sale of land auction results when a default occurs (Study on Decision Number: 121/Pdt.G.2017/PN.Unr) according to the creditor, according to the applicable procedure. However, this is different from the opinion of the Debtor who feels that the auction process carried out by the Creditor is detrimental to the Debtor because the auction limit value for land objects is not appropriate because it is far below the market and the auction sales results are not notified by the Creditor to the Debtor.The value of justice in fulfilling the price of the auction sale of land rights in the event of default, is to fulfill the benefits for both the Debtor and the Creditor, the Creditor benefits in returning the money lent to the Debtor. Meanwhile, the debtor who is in default will feel that he is getting justice if the debt burden is paid off and when the collateral is sold through auction, he still gets the remainder.Keywords: Auction; Default; Land; Sale.